2016
DOI: 10.2174/1874210616021001360
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Lipid Content in Liposome-Encapsulated Nisin Improves Sustainable Bactericidal Activity against Streptococcus mutans

Abstract: An oral infectious disease, dental caries, is caused by the cariogenic streptococci Streptococcus mutans. The expected preventive efficiency for prophylactics against dental caries is not yet completely observed. Nisin, a bacteriocin, has been demonstrated to be microbicidal against S. mutans, and liposome-encapsulated nisin improves preventive features that may be exploited for human oral health. Here we examined the bactericidal effect of charged lipids on nisin-loaded liposomes against S. mutans and inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In a study, comparing both negatively and positively charged lipid NPs loaded with Nisin, a bacteriocin, the positively charged LNPs with Nisin showed stronger bactericidal property compared to the 'as-prepared' and negatively charged LNPs against S. mutans and released the bacteriocin in a controlled fashion for a longer time. 190 In a similar study against S. mutans, 100 pmol Nisin-loaded LNPs completely inhibited the glucanbiofilm synthesis, which is a preferred mechanism for survival and colonization by bacterial species. In addition, the delivery of the Nisin via LNPs reduced the inhibitory concentration by a factor of 4 when compared to pure Nisin.…”
Section: For Dental Caries (Supragingival) Preventionmentioning
confidence: 93%
“…In a study, comparing both negatively and positively charged lipid NPs loaded with Nisin, a bacteriocin, the positively charged LNPs with Nisin showed stronger bactericidal property compared to the 'as-prepared' and negatively charged LNPs against S. mutans and released the bacteriocin in a controlled fashion for a longer time. 190 In a similar study against S. mutans, 100 pmol Nisin-loaded LNPs completely inhibited the glucanbiofilm synthesis, which is a preferred mechanism for survival and colonization by bacterial species. In addition, the delivery of the Nisin via LNPs reduced the inhibitory concentration by a factor of 4 when compared to pure Nisin.…”
Section: For Dental Caries (Supragingival) Preventionmentioning
confidence: 93%
“…Such a system could reduce nephrotoxicity caused by free vancomycin, while enhancing the effect in lung infection. Similarly, nisin encapsulated into cationic liposomes exhibited efficient microbicidal activity against S. mutans [165].…”
Section: Liposomesmentioning
confidence: 99%
“…Thus, the advantages of these delivery systems have made them attractive for the treatment of dentistry diseases. Their use have been described for prevention of caries and periodontitis through the disruption of oral biofilms [ 66 , 67 , 92 , 93 , 94 ], reduction in acid erosion [ 95 ], and enhancement of the biomineralization for dental tissue regeneration [ 68 , 96 ].…”
Section: Drug Delivery Systems Used In the Prevention And Treatment O...mentioning
confidence: 99%
“…Furthermore, in vitro assay indicated a higher antimicrobial activity of cationic liposomes when compared with the control group (2-fold higher), which was greater than non-ionic and anionic liposomes (1.3- and 0.6-fold, respectively). The results demonstrated that the electrostatic interaction between liposomes and bacterial membranes can be a great strategy to enhance oral retention and improve the activity against microorganisms [ 66 ].…”
Section: Drug Delivery Systems Used In the Prevention And Treatment O...mentioning
confidence: 99%